Effect of seeding depth on the emergence of tomato (Lycopersicon esculentum Mill.) seedlings (Scientia Agricola, 1994)
The effect of seeding depth on the emergence of tomato (Lycopersicon esculentum Mill.) seedlings variety Tropic was tested for 0.5; 1.5; 2.5; 3.5; 4.5, and 5.5 cm depth of seeding in soil and sand medium, at a 3:1 ratio with a constant water content around 70% of field capacity. The experimental design was totally randomized with four replications of 50 seeds per treatment, quantifying the depth effects by determining the emergence time and percentage of the final stand. The results showed that the 1.5 cm seeding depth provided an emergence time and a final stand significantly higher than the others, thus being considered as ideal for tomato seeding.